Prevalence and Risk Factors for Sexually Transmitted Infections in Gay and Bisexual Prostate Cancer Survivors: Results From the Restore-2 Study - Wheldon, Christopher W.; Polter, Elizabeth; Rosser, B. R. Simon; Bates, Alex J.; Haggart, Ryan; Wright, Morgan; Mitteldorf, Darryl; Ross, Michael W.; Konety, Badrinath R.; Kohli, Nidhi; Talley, Kristine M. C.; West, William; et al. (Frontiers in Oncology, 2022)
Background Equitable cancer survivorship care for gay and bisexual male (GBM) prostate cancer survivors should be responsive to their sexual health needs. Rates of sexually transmitted infections (STIs) are higher among GBM compared to heterosexual men across the lifespan. In addition, evidence suggests that GBM will use a variety of strategies to cope with sexual dysfunction that may increase risk for STIs. The purpose of this study was to determine the prevalence of STIs following prostate cancer treatment among GBM and identify risk factors. Methods In 2019, 401 GBM previously treated for prostate cancer were recruited into the Restore-2 Study. They completed a baseline online questionnaire with items assessing STIs diagnosed since being treated for prostate cancer. Any STI diagnoses was regressed on demographic, clinical, and relationship related variables using binary logistic regression. Results Forty-five participants (11.4%) were diagnosed with an STI during or following their prostate cancer treatment. The mostly commonly diagnosed STI was syphilis (4.3%), followed by gonorrhoea (2.8%), and chlamydia (2.5%). Four participants were infected with HIV following their prostate cancer treatment. Independent risk factors for STI diagnosis included time since prostate cancer diagnosis (aOR = 1.18; 95% CI: 1.10-1.26), nonmonogamous sexual relationship (aOR = 11.23; 95% CI: 2.11-59.73), better sexual function (aOR = 1.02; 95% CI: 1.01-1.04), penile injection treatment (aOR = 3.28; 95% CI: 1.48-7.29), and multiple sex partners (aOR = 5.57; 95% CI: 1.64-18.96). Conclusions GBM prostate cancer survivors are at risk for STIs. Culturally responsive STI prevention should be incorporated into cancer survivorship plans, particularly as men are treated for and regain sexual function over time.